Isolation and Molecular Identification of Potential Probiotic Yeast Strains Found in Malaysian Kefir Drinks Samples - Mohd Akmal, Azhar; Dr. Mimi Sakinah, Abdul Munaim (2019)
Kefir drink is a product from the fermentation process of milk using symbiotic mixture of bacteria and yeast consortium. Saccharomyces and lactobacillus are the major genera found in the kefir drink. The present work involves the isolation and identification of potential probiotic yeast strains in the kefir drink samples from Malaysia. The molecular identification was done by PCR using ITS1 and ITS4 amplified regions. Nine different yeast strains were isolated, and the strains were successfully identified based on the sequence analysis. Saccharomyces and Kodamaea were found to be the major population in the kefir drink samples. Lastly, kefir milk is one of the excellent sources of probiotic yeast strains and could be used as a new yeast probiotic formulation or in food supplements. Moreover, the amplification of ITS region can be used as a useful method to identified yeast strains.